Carbonate REE plus Y signatures from the restricted early marine phase of South Atlantic Ocean (late Aptian - Albian): The influence of early anoxic diagenesis on shale-normalized REE plus Y patterns of ancient carbonate rocks - Caetano-Filho, Sergio; Paula-Santos, Gustavo M.; Dias-Brito, Dimas [UNESP] (Elsevier B.V., 2018)
Rare earth elements plus yttrium have been extensively applied in paleoenvironmental studies of ancient carbonate successions due to their fractionation in the marine environment. However, in modem marine anoxic environments, seawater REE + Y signatures can be suppressed in reducing conditions (e.g. stagnant basins and/or early diagenesis) by REE remobilization from several sedimentary components (e.g. detrital siliciclastics, oxides, organic compounds). We present the shale-normalized REE + Y signatures for a transgressive marine carbonate succession of the primitive South Atlantic Ocean (latest Aptian-Albian), in a restricted marine setting with anoxic bottom conditions, to provide and evaluate the REE + Y record deposited in such conditions. Based on well-constrained paleoenvironmental reconstruction through microfacies analysis, three shale normalized REE + Y patterns were identified, varying according to the microfacies associations (MA) and related diagenetic environments: a) light REE-enriched patterns in the more proximal MA associated with burial diagenesis at the base of section; b) flat patterns towards distal MA related to anoxic and sulfidic early diagenesis; and c) middle REE-enriched patterns in MA related to dissolution of Fe-Mn oxy-hydroxide grains under reducing early diagenesis. Cerium anomalies are absent due to stagnant water mass conditions, in accordance with previous studies for the early marine South Atlantic. Y/Ho ratios are lower than modem seawater values, with an increasing trend towards more distal facies. The non-seawater shale-normalized REE + Y patterns of the marine carbonates from the primitive South Atlantic Ocean corroborate studies in modern marine reducing environments, in which REE can be remobilized from detrital phases, oxides and organic compounds, suppressing the primary seawater REE Y signature of authigenic minerals. Caution is suggested for the sole use of carbonate REE + Y signatures as paleoenvironmental proxies, especially in ancient successions lacking proper microfaciological components.
Keywords: Rare earth elements; Paleoceanography; Paleoenvironments; Campos Basin; Redox proxies